The Practice of QRIS Usage in Traditional Vegetable Vendor Transactions: An Ethnomethodological Approach for Payments - Nur Rahma; Wa Ode Rayyani (Jurnal Bisnis dan Pemasaran Digital, 2025)
Purpose: This study examines the internal logic and daily practices that traditional vegetable vendors use when adopting the Quick Response Code Indonesian Standard (QRIS) payment system, viewed through social methods that sustain the people's economy in the digital era.Methodology: A qualitative field study employing an ethnomethodological approach was conducted. Primary data were collected through in depth interviews and participant observation of vegetable vendors operating in a traditional market. Data analysis followed four stages, namely indexicality analysis, reflexivity analysis, conceptual action analysis, and the presentation of common sense knowledge.Results: Vendors interpret the QRIS sticker as an index of modernity that signals service readiness to younger, cash averse buyers. Through reflexive accounts, vendors justify QRIS use as a practical solution to the classic problems of providing small change and accepting counterfeit currency, even though delayed fund settlement and unstable market internet connections continue to constrain daily capital liquidity.Conclusions: QRIS improves the transparency and operational efficiency of micro enterprises, yet its integration remains complementary rather than substitutive, since the market ecosystem still rests on social capital and interpersonal trust. Limitations: Findings are contextually bound to a single commodity group and cannot be statistically generalized. Contributions: The study offers regulators and financial institutions an insider perspective for designing contextually adaptive digital infrastructure and outreach programs.